Dreaming and the weighted cognitive Rolodex: A review of The Emergence of Dreaming by William G. Domhoff - Tuominen Jarno. (Universitaet Heidelberg - Central Institute of Mental Health, 2022)
In his new book the eminent dream researcher William G. Domhoff restates the neurocognitive theory of dreams. It provides a lucid overview of decades of empirical research, combining it with recent neuroscientific research to form a theoretical whole. Providing a clear account of his theory Domhoff pivots the science of dreaming onwards, by posing a challenge for competing views.
Domhoff, W.G. (2017). The Emergence of Dreaming: Mind-wandering, embodied simulation, and the default network. New York: Oxford University Press.